Government accounting reports for the citizen: a reinterpretation of the general balance sheet for the State of Goiás, Brazil - Diana Vaz de Lima; Karina Evangelista Cruz; Rafiza Luziani Varão Ribeiro; Ricardo Borges de Rezende; Valquíria Andrade de Souza (Revista Ambiente Contábil)
Purpose: The objective of this article is to present the reinterpretation process of the General Balance Sheet 2022 for the government of Goiás, a Federative Unit of Brazil located in the Midwest region, based on popular financial reports (PFRs).